2007
DOI: 10.1186/1476-072x-6-22
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS in Russia: determinants of regional prevalence

Abstract: Background: The motivation for this paper is to inform the selection of future policy directions for tackling HIV/AIDS in Russia. The Russian Federation has more people living with HIV/AIDS than any other country in Europe, and nearly 70% of the known infections in Eastern Europe and Central Asia. The epidemic is particularly young, with 80% of those infected aged less than thirty, and no Russian region has escaped the detection of infections. However, measures to address the epidemic in Russia have been hampe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…Several studies have examined the socioeconomic factors associated with HIV prevalence and injecting drug use in Russia. Moran et al investigated the relative importance of several variables in influencing HIV prevalence in a cross-sectional study based solely on Russian federal government statistics [ 78 ]. The authors found urbanization, mobility, crime, and income growth associated with HIV prevalence.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have examined the socioeconomic factors associated with HIV prevalence and injecting drug use in Russia. Moran et al investigated the relative importance of several variables in influencing HIV prevalence in a cross-sectional study based solely on Russian federal government statistics [ 78 ]. The authors found urbanization, mobility, crime, and income growth associated with HIV prevalence.…”
Section: Methodsmentioning
confidence: 99%
“…Integrating multiple-level influences requires methods that capture the processes that take place between distal and proximal antecedents of HIV-related behaviors and translate them into meaningful predictions. Observations of the trajectory of the AIDS epidemic and between-region comparisons have helped to identify the impact of several structural factors on the course of the HIV epidemic (e.g., increases in HIV prevalence during war [61] or higher HIV prevalence associated with income inequality [62, 63]). Prospective studies following structural changes could further discover how different levels of factors respond to new structural configurations.…”
Section: Discussionmentioning
confidence: 99%
“…While this paper has discussed some of the societal and attitudinal challenges that will need to be addressed when expanding HIV programmes in the former Soviet Union, it is important to remember that the factors that contributed to the spread of HIV in the region include the large-scale social and economic changes associated with transition (38), as well as the rapid diffusion of injecting drug use (19). Furthermore, it is worth noting that there are substantial differences across and within the different countries of this part of Europe.…”
Section: Discussionmentioning
confidence: 99%